Legal education in the history of pedagogical thought - Sarsekeyeva, Zh.Ye.; Odintsova, S.A.; Odintsova, Ye.A. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The paper discusses the views of philosophers, scientists and educators on law and legal education of the individual in different historical periods. The authors reveal that the system of legal education is determined by the character and policy of the state and that the right in a democratic society is treated as an important element of the citizen education. The emergence of the issue of law education and the variations of its solution is associated with the extensive process of social development. Accordingly, legal education in the history of educational thought is often seen as part of civic education. These areas of education have much in common, but legal education focuses to a great extent on the conscious discernment of legal laws, regulations and responsibilities.
Педагогикалық ойлар тарихындағы құқықтық тəрбие
Правовое воспитание в истории педагогической мысли
Keywords: citizen; society; law; human rights; legal education; civic education; sense of justice; pedagogical views; pedagogical research; history of pedagogy